Outcomes and Resource Use Among Overweight and Obese Children With Sepsis in the Pediatric Intensive Care Unit. (May 2020) - Peterson, Laura S.; Gállego Suárez, Cecilia; Segaloff, Hannah E.; Griffin, Cameron; Martin, Emily T.; Odetola, Folafoluwa O.; Singer, Kanakadurga
Objective: To evaluate the effect of overweight and obesity on outcomes and resource use among patients with sepsis in the pediatric intensive care unit (PICU). Design: Retrospective analysis of clinical characteristics, resource use, and mortality among children 0 to 20 years of age admitted to the C.S. MottChildren's Hospital PICU (University of Michigan) between January 2009 and December 2015, with a diagnostic code for sepsis at admission (based on International Classification of Diseases, Ninth Revision - Clinical Modification codes) and with weight and height measurements at PICU admission. Measurements and Main Results: A total of 454 participants met the inclusion criteria. Seventy-six were categorized as underweight (body mass index [BMI] percentile <5th) and were excluded, which left a final sample size of 378 participants. Children with a BMI> 5th and <85th percentiles for age were categorized as normal weight and those with a BMI> 85th percentile as overweight/obese. After descriptive and bivariate analyses, multivariate regression methods were used to assess the independent effect of obesity status on mortality and the use of PICU technology after adjustment for patient age and illness severity at admission. Of the 378 patients studied, 41.3% were overweight/obese. There was no difference in microbiologic etiology of sepsis ( P = .36), median PICU length of stay in days (5.4 vs 5.6; P = .61), or PICU mortality (6.4% vs 7.2%; P = .76) by weight status. The use of specialized PICU technology including extracorporeal membrane oxygenation (odds ratio [OR]: 2.77, 95% confidence interval [CI]:1.13-6.79) and continuous renal replacement therapy (OR: 4.58, 95% CI: 1.16-18.0) was higher among overweight/obese patients, compared with normal weight patients. Conclusions: Although PICU mortality and length of stay were similar for obese–overweight patients and normal weight critically ill children with sepsis, there was significantly higher use of specialized organ-supportive technology among obese patients, likely indicating higher occurrence of multiple organ dysfunction.